Paternalism and Identity: The Role of Personal Labour Organization in the Formation of Group Identity Among the Metis in the Rupertsland Fur Trade and the Aboriginal People in the Northern Australian Cattle Industry - Parker, Leanna (University of Saskatchewan, 1999)
The question of the origins of a Metis identity in Canada is one that has been contemplated by several scholars. These scholars have taken various approaches to the question, many focusing solely on the social and political aspects of Metis history. While such approaches can be useful, they ignore the crucial influence of the economic and labour relations of the Rupertsland fur trade in the development and expression of a distinct Metis identity in western Canada. The unique economic and labour relations of the Rupertsland fur trade, identified by H. Clare Pentland as personal labour relationships, allowed a cohesiveness and inter-connectedness to develop between the Aboriginal labourers and their European employers which emphasized the interdependencies inherent in the industry. However, while personal labour relations were an important catalyst for the development and expression of a distinct Metis identity, it is too simplistic to suggest that it was these relations alone that encouraged such a phenomenon. The northern Australian cattle industry utilized similar economic and labour relations and yet a distinct mixed descent identity did not develop in Australia. Therefore, the external influences in the industry must also be examined. The four most important external influences that encouraged the development of a Metis identity in Canada and discouraged a similar event in Australia were: the needs of the colonial employers in regards to land tenure; the economic opportunities available to the people of mixed descent; the educational opportunities available to the people of mixed descent; and, the time depth of contact in both industries. These four external influences combined with the use of personal labour organization in the Rupertsland fur trade encouraged the development and expression of a distinct Metis identity in Canada.